Pengaruh Penerapan Media Pembelajaran Berbasis Aplikasi Teachmint Terhadap Hasil Belajar Siswa di Kelas XI DKV pada Mata Pelajaran Fotografi Digital di SMK PGRI Ciawigebang - Hidayah, Ade Arif; Setiawan, Dena Latif (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to analyze the influence of the application of Teachmint application-based learning media on student learning outcomes in grade XI Visual Communication Design (DKV) in the subject of Digital Photography at SMK PGRI Ciawigebang. The use of technology in education, especially learning applications, is increasingly important in supporting an effective and efficient learning process. The Teachmint app was chosen because of its interactive features that are expected to increase student engagement and improve learning outcomes. The research method used is pre-experiment with one group design pre-test and post-test. Data was collected through learning outcome tests before and after the intervention, as well as observations and questionnaires to measure students' responses to the use of the Teachmint application. The results of the study show that there is an increase in student learning outcomes after the implementation of Teachmint application-based learning media at SMK PGRI Ciawigebang. There is a significant difference between student learning outcomes before and after using Teachmint-based learning media. Based on the results of the descriptive analysis, the average pretest scores of students were obtained 52.50 and 72.19, this means that the difference in student learning outcomes using learning media based on the teachmint application before and after learning